Monitoring System for Levels of Voltage, Current, Temperature, Methane and Hydrogen in IOT-Based Distribution Transformers (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The distribution network is an integral part of electricity distribution, both technically and non-technically, which is very vulnerable to disturbances. This disturbance should be resolved as soon as possible so that it does not interfere with the performance of the electricity distribution and also damage the distribution transformer. In overcoming this disturbance, it can be done by using a safety device and a voltage breaker in each load area. The protection system in the distribution network must work quickly and immediately isolate abnormal conditions to prevent further damage and minimize blackouts. This disturbance should be resolved as soon as possible so that it does not interfere with the performance of the electricity distribution and also damage the distribution transformer. . The effects of this disturbance are changed in voltage, current, temperature, and gas levels in the distribution transformer. So we need a tool that can monitor the condition of the transformer. NodeMCU ESP8266 is a microcontroller that can connect to the internet network, which is used as the central control. The PZEEM-004T sensor is applied as a current and voltage reader. For gas measurement, the MQ-4 sensor is used to measure CH4 gas levels; the MQ-7 sensor is used to measure CO gas levels, and the MQ-8 sensor is used to measure H2 gas levels. The test results found that due to the unbalanced load conditions, there was an increase in temperature in the transformer, which resulted in changes in gas levels. Where from the test, it was found that the lowest gas content was CH4 reaching 113 PPM, CO went 21PPM, and H2 reaching 158PPM.